Lignin-modified road marking paint: weathering aging studies - Pereira,Amanda Petronilha (2021)
Abstract The accelerated artificial aging with ultraviolet radiation, viscosity, density, no-pick-up time, flexibility, and abrasion resistance of lignin-modified road marking paint were evaluated. The addition of lignin did not cause significant changes in the physical chemistry, flexibility and no-pick-time test compared to the precursor paint. The addition of 1.00 wt. % of lignin increased the abrasion resistance by 36%. The Fourier Transform Infrared technique performed before and after exposure to Weather-o-meter aging chamber has shown the cleavage of ester groups that are present in acrylic-based resin. The incorporation of 0.10 wt.%, 0.25 wt.%, and 1.00 wt.% increased the photodegradation resistance of the road marking paint inhibiting the ester group and side-chain scissions, since the C-O and C=O band intensity increased after irradiation. The introduction of lignin delayed the yellowing of the aged samples and improved mechanical and photophysical properties besides being a good strategy for the biomass waste utilization of the paper industry.